Prospects of forming health-saving educational environment of elementary school - T.V. Vodolazska (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose : to present the results of a special study group of primary school teachers of Poltava region. To substantiate the conditions of formation of health saving educational field of elementary school. Material : the study involved 78 teachers from 14 schools of the Poltava region. Results : is investigated the effect of the educational field on the health of primary school children, are highlighted the essential characteristics of health saving educational field. On the basis of analysis of the data by the research team are considered: the components of the field which affect on the health of students, the development trends of health saving educational field of elementary school. Conclusions : the prospects for development of health saving educational field should be a transformation class-lesson system, the creation of multifunctional educational field, the use of health saving learning technologies, change of the evaluation system of personal students` achievements, the use of integrated assessment of the junior schoolboy emotional sphere, the development of new forms of cooperation between the teacher and the students.